Evaluation of drop vertical jump kinematics and kinetics using 3D markerless motion capture in a large cohort - Templin, Tylan; Riehm, Christopher D.; Eliason, Travis; Hulburt, Tessa C.; Kwak, Samuel T.; Medjaouri, Omar; Chambers, David; Anand, Manish; Saylor, Kase; Myer, Gregory D.; Nicolella, Daniel P. (Frontiers in Bioengineering and Biotechnology, 2024)
3D Markerless motion capture technologies have advanced significantly over the last few decades to overcome limitations of marker-based systems, which require significant cost, time, and specialization. As markerless motion capture technologies develop and mature, there is increasing demand from the biomechanics community to provide kinematic and kinetic data with similar levels of reliability and accuracy as current reference standard marker-based 3D motion capture methods. The purpose of this study was to evaluate how a novel markerless system trained with both hand-labeled and synthetic data compares to lower extremity kinematic and kinetic measurements from a reference marker-based system during the drop vertical jump (DVJ) task. Synchronized video data from multiple camera views was co-recorded with marker-based data from 127 participants who performed three repetitions of the DVJ. Root mean squared error values of lower limb joint angles and joint moments were ≤ 9.61 degrees and ≤ 0.23 Nm/kg, respectively. Pearson correlation values between markered and markerless systems were 0.67-0.98 hip, 0.45-0.99 knee and 0.06-0.99 ankle for joint kinematics. Likewise, Pearson correlation values were 0.73-0.90 hip, 0.61-0.95 knee and 0.74-0.95 ankle for joint kinetics. These results highlight the promising potential of markerless motion capture, particularly for measures of hip, knee and ankle rotations. Further research is needed to evaluate the viability of markerless ankle measures in the frontal plane to determine if differences in joint solvers are inducing unanticipated error.